Rice husk ash silica as a potential drug carrier - Muhammad Shuib, Nur Azfa; Darnis, Deny Susanti; Mohamed Iqbal, Mohammad Anwar; Miskam, Mazidatulakmam (2015)
Rice husk is a by-product from rice mills that are often regarded as an agricultural waste and practically has no commercial value. However, rice husk ash (RHA) obtained from the calcination of rice husk at elevated temperature offers a greener, safer and cheaper source of silica precursor. Currently used silica precursor such as tetraethyl ortosilicate (TEOS) and sodium silicate are relative expensive and dangerous to human and environmental. RHA has been widely used as a silica support in heterogeneous catalysis but its capability as a drug carrier has not been explored. Thus, in this study we intended to investigate the properties of RHA-silica prepared via sol-gel as a potential drug carrier. The BET surface analysis measured the surface area to be 589 m2/g and the pore diameter as 5.1 nm. Based on the pore diameter, the RHA-silica is classified as mesoporous. The X-ray powder diffraction (XRD) showed that the RHA-silica is in amorphous form. The Fourier Transform Infrared Spectroscopy did not detect the presence of any organic moieties that are not related to silica which indicated the RHA-silica obtained is a pure silica. Based on these preliminary results, it can be said that the RHA-silica has potential to be used as a drug carrier.